Evaluation of COVID-19 Vaccine Refusal among AOU Students in Kuwait and their Families and their Expected Inclination Towards the Acceptance or Refusal of the Vaccine - AL-Shalabi, Luai (International Journal of Statistics in Medical Research, 2022)
The purpose of this research was to determine the factors influencing the refusal of a coronavirus disease (COVID- 19) vaccine among adult students from Arab Open University in Kuwait (AOU) and their families and to study the trends of reluctant participants. A questionnaire was conducted (n = 691; aged 12 and older). Significant factors and the tendency of hesitant participants to accept or reject the vaccine were explored by applying a cleaning and coding process, a rough set theory (RS), a decision tree (DT) classifier, and a p-value. Overall, 18.4% of the participants reported refusing to receive a COVID-19 vaccine, while 17.2% were uncertain. The study shows that hesitant subjects represent a tendency to accept vaccination. Of the vaccine-refusal participants, subjects aged 18-29, suffer from chronic disease, were infected with COVID-19, were vaccinated against seasonal flu, and had concerns about receiving a COVID-19, representing 44.1%, 21.05%, 16.76%, 54.33%, and 70.08%, respectively. Overall, 18.4% of the participants demonstrated a refusal to receive a COVID-19 vaccine and 17.2% are hesitant. Factors influencing the level of acceptance/rejection of the vaccine were determined. The results showed that hesitant participants have a strong tendency to accept the vaccine (81.82%). Since vaccination is an important strategy to reduce the spread of the COVID-19 pandemic, the ministry of public health must immediately address the significant factors for the acceptance/rejection of the vaccine, as well as the trend of hesitant participants toward the acceptance of the vaccine.